Dukungan Keluarga dan Self Efikasi terhadap Self Manajemen Penderita Hipertensi - Arvida. Bar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the relationship between family support and self-efficacy on self-management of hypertension sufferers. This research method is cross-sectional research. The results showed that respondents with high self-efficacy dominantly have good self-management (64.2%). In low self-management, the dominant has less self-management (57.2%). In the excellent category of family support variables, the chief has good self-management (61.1%). The dominant has less self-management (57.1%) with less family support. The chi-square test results show that self-management is related to family support (p-value=0.001), self-efficacy (p-value=0.006). In conclusion, self-management of hypertensive patients tends to increase if the patient gets high family support and self-efficacy. Keywords: Family Support, Hypertension, Self Efficacy, Self Management